Design and experimental study of a buckling-restrained steel plate shear wall with novel buckling-restrained panels for improving bearing capacity and energy dissipation. (1st October 2021) - Li, Zuohua; Ge, Lei; Qi, Yihe; Geng, Yan; Teng, Jun
Highlights: The BRSPSW-NBP with improved bearing capacity and energy dissipation was proposed. Theoretical analyses were conducted to study the seismic behaviour of BRSPSW-NBP. A BRSPSW-NBP specimen and a BRSPSW specimen were cyclically tested. The performance of BRSPSW-NBP specimen were improved. Abstract: In this study, a buckling-restrained steel plate shear wall with novel buckling-restrained panels (hereafter referred to as the BRSPSW-NBP) with improved bearing capacity and energy dissipation is proposed. The novel buckling-restrained panel comprises a concrete panel and load-bearing connection steel plates with energy dissipation segments. These steel plates are connected with the boundary frame through connectors for transferring the horizontal and vertical loads to the concrete panel. Therefore, the buckling-restrained panel serves as an additional load-bearing component that increases the bearing capacity and lateral stiffness of the BRSPSW-NBP. To dissipate seismic energy, the energy dissipation segments in the load-bearing connection steel plates are designed to undergo plastic deformation earlier than the inner steel plate such that the BRSPSW-NBP develops a multi-stage energy dissipation characteristic. Theoretical analyses were conducted to investigate the seismic behaviour of the BRSPSW-NBP. The bearing capacity and multi-stage energy dissipation characteristic of the BRSPSW-NBP were studied through quasi-static testing. The results demonstrated that the connection steel plates with energy dissipation segments share the horizontal and vertical loads of the BRSPSW-NBP and undergo plastic deformation earlier than the inner steel plate, thus improving the bearing capacity and energy dissipation performance of the BRSPSW-NBP.